A systematic review of emotion regulation in parent-mediated interventions for autism spectrum disorder - Hendrix, Nicole M.; Pickard, Katherine E.; Binion, Grace E.; Kushner, Elizabeth (Frontiers in Psychiatry, 2022)
Autistic individuals are at elevated risk for difficulties with emotion regulation (ER) that emerge early in life and are associated with a range of internalizing and externalizing disorders. Existing interventions that support ER have focused on school-age autistic children and adolescents as well as adults. Preventative approaches to improving ER in early childhood are thus needed, as is understanding the approaches by which ER skills can be feasibly supported in this young population. This review summarizes how ER has been measured within parent-mediated interventions for children at or under the age of 6 years and the extent to which ER is measured concurrently with or distinctly from challenging behavior. We searched PsycInfo, EBSCOhost, and PubMed databases through August 2021 in peer reviewed journals for parent-mediated interventions targeting either ER and/or challenging behavior. The systematic search resulted in 4,738 publications, which following multi-stage screening, yielded 20 studies. Eighteen of 20 studies were designed to target challenging behavior using manualized curricula or behavior analytic methodologies and assessed child outcomes through validated caregiver rating scales and/or direct behavioral observation. One study measured changes in ER as secondary to the social communication skills that were targeted in the intervention. Only one study specifically targeted ER skill development and measured changes in ER as the primary intervention outcome. Findings highlight the need for better assessment of ER outcomes within the context of parent-mediated interventions for toddlers and young autistic children.